Evaluation Of The Impact Of Educational Intervention On Traditional Beliefs, Knowledge, Attitude And Practice About Childhood Diarrhea And Its Management Among Mothers In Morang, Nepal - Ansari, Mukhtar (2012)
Diarrhea is a global problem including Nepal and it is the second leading cause of child death worldwide. In Nepal, diarrhea is still a common problem and is a national priority despite the government’s efforts to reducing mortality for children under five through implementation of a childhood diarrheal diseases control program. The study was conducted with the objective of evaluating mothers' beliefs, knowledge, attitudes and practices about childhood diarrhea and its management with the final intention to reduce childhood diarrhea mortality and morbidity.